2023
DOI: 10.1080/02670836.2022.2160532
|View full text |Cite|
|
Sign up to set email alerts
|

Creep and mechanical properties of aluminium A356 composites reinforced with coated and un-coated MWCNTs fabricated using the stir casting method

Abstract: Multi-walled carbon nanotubes (MWCNTs) possess outstanding physical and mechanical properties, making them suitable as reinforcing materials for metal-matrix composites. However, their creep resistance has not been studied well. In the present study, aluminium A356 composites reinforced with various weight percentages of MWCNTs were fabricated using the stir casting technique. The surface coating was applied to enhance the wettability of carbon nanotubes. Tensile experiments, fracture analysis, creep tests, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Metal matrix nanocomposites (MMCs) reinforced by CNTs [ 5 , 6 , 7 ], which can serve in a high-temperature environment, have great potential in electronic, aerospace, and other industries. Experimental studies [ 8 , 9 ] have reported that only a small addition of CNT could result in a significant enhancement in mechanical properties of metals. Among MMCs, CNT reinforced copper (CNT/Cu) nanocomposites gain considerable attention due to their excellent electrical and thermal conductivity as well as high strength.…”
Section: Introductionmentioning
confidence: 99%
“…Metal matrix nanocomposites (MMCs) reinforced by CNTs [ 5 , 6 , 7 ], which can serve in a high-temperature environment, have great potential in electronic, aerospace, and other industries. Experimental studies [ 8 , 9 ] have reported that only a small addition of CNT could result in a significant enhancement in mechanical properties of metals. Among MMCs, CNT reinforced copper (CNT/Cu) nanocomposites gain considerable attention due to their excellent electrical and thermal conductivity as well as high strength.…”
Section: Introductionmentioning
confidence: 99%